2020
DOI: 10.1080/13880209.2020.1738504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naringenin on the pharmacokinetics of tofacitinib in rats

Abstract: Context: Naringenin and tofacitinib are often used together for treatment of rheumatoid arthritis in Chinese clinics. Objective: This experiment investigates the effect of naringenin on the pharmacokinetics of tofacitinib in rats. Materials and methods: Twelve Sprague-Dawley rats were randomly divided into two groups (experimental group and control group). The experimental group was pre-treated with naringenin (150 mg/kg/ day) for two weeks before dosing tofacitinib, and equal amounts of CMC-Na solution in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Compared with the control group, pre-treatment of rats with naringenin for 2 weeks could increase the AUC, MRT, and T max values of tofacitinib by 1.76-fold, 1.60-fold, and 4.00-fold, respectively, but decreased its CL z/F by 1.69-fold. 20 Similarly, metabolisms of both ibrutinib and felodipine were inhibited, and their systemic exposures were also increased when co-administrated them with naringenin. It was supposed that naringenin might affect these two drugs by inhibiting the CYP3A4mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, pre-treatment of rats with naringenin for 2 weeks could increase the AUC, MRT, and T max values of tofacitinib by 1.76-fold, 1.60-fold, and 4.00-fold, respectively, but decreased its CL z/F by 1.69-fold. 20 Similarly, metabolisms of both ibrutinib and felodipine were inhibited, and their systemic exposures were also increased when co-administrated them with naringenin. It was supposed that naringenin might affect these two drugs by inhibiting the CYP3A4mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The DDIs and HDIs are generally achieved by the pharmacokinetic properties, and may occur in the phase of absorption, distribution, metabolism or excretion. The CYP450 system is crucial for drug metabolism which is related to the metabolism of endogenous substances, detoxi cation of exogenous substances and activation of precarcinogens [13]. CYP450 superfamilies include CYP1, CYP2 and CYP3.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, with the development of combine therapy of medicines, increasingly importance has been attached to drug-drug interactions (DDIs) and herbal-drug interactions (HDIs). Several studies on the DDIs and HDIs have been reported in the last few years [12][13][14]. Some ingredients could inhibit or induce the activities of drug-metabolizing enzymes or transporter proteins, which may change the absorption, distribution, metabolism and excretion of drugs, effecting its pharmacological activity and toxicity on concomitant administration.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the PK-PD models were conducted successfully by combining PK and PD data collected after oral administration of WBC. (Zhang et al, 2016;Wang, Shen, et al, 2020).…”
Section: F I G U R Ementioning
confidence: 99%